Dampak Capital Structur, Liquiditas, Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan - Prakoso, Sajiwo Tri (JURNAL MANAJEMEN DAN BISNIS, 2024)
The research was conducted to find empirical evidence about the variables of capital structure, liquidity, firm size and profitability to firm value. The data used uses the manufacturing industry sector listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The variables used are capital structure with DER indicator, Firms Size with ln indicator (total Asset), liquidity with current ratio indicator and profitability with ROA indicator, the dependent variable using firm value with PBV indicator. The type of data with secondary data is taken from the financial statements of 27 public companies with multiple regression analysis. The results show that capital structure, liquidity, firm size and profitability have an influence on firm value